Evaluation of Antagonistic Activity of Endophytic Bacteria from Dayak Onion Against Ganoderma boninense - Desiana Sinta; Norwahyunie Norwahyunie; Noraini Noraini; Zulviana Zulviana; Frans Grovy Naibaho; Vinsen Willi Wardhana; Desimaria Panjaitan; Adrian Hartanto (Bioactivities, 2024)
Basal stem rot (BSR) is one of the key contributors to the decline in palm oil production in Indonesia. BSR is caused by the pathogenic plant fungus Ganoderma boninense. Currently, the control of G. boninense growth relies on systemic fungicides. However, systemic fungicides have negative impacts as they can harm natural soil microorganisms. Biocontrol agents present an environmentally friendly alternative for G. boninense management. The objective of this research was to select and identify endophytic bacterial isolates from Dayak onion [Eleutherine bulbosa (Mill.) Urb.] with antagonistic activity against G. boninense. The investigation was initiated with the isolation of 34 endophytic bacterial isolates and G. boninense isolate. The hemolytic capabilities of endophytic bacterial isolates were evaluated on blood agar media. Antagonism assessments were conducted through the dual-culture method, and the inhibition of G. boninense was measured using the percentage inhibition of radial growth (PIRG). The endophytic bacteria exhibiting the highest PIRG values were identified through molecular analysis based on the 16S rRNA gene sequence. Results revealed that 27 isolates demonstrated no ability to hydrolyze blood agar (gamma hemolysis) indicating no pathogenicity. Isolate CED9 demonstrated the highest PIRG value at 70.26%. Genomic identification based on the 16S rRNA gene sequence confirmed that isolate CED9 was classified as Bacillus subtilis. The identification of biocontrol agents from Dayak onion represents valuable information and a potential arsenal for future strategies in mitigating (BSR) disease.